Specific inhibitors of mammalian DNA polymerase species - Mizushina, Y.(Kobe Gakuin Univ. (Japan). Department of Nutritional Science) (Bioscience, biotechnology, and biochemistry, 2009)
In screening of selective inhibitors of eukaryotic DNA polymerases (pols) for 15 years, more than 100 inhibitors have been discovered from natural and chemical sources. Some compounds selectively inhibit the activities of mammalian pols, and in particular, dehydroaltenusin and curcumin derivatives, such as monoacetyl-curcumin, were found to be specific inhibitors of pol α and pol λ, respectively. Dehydroaltenusin was isolated from a fungus (Alternaria tennuis), and this compound inhibited cell proliferation of human cancer cell lines by arresting the cells at the S-phase, and was effective in suppressing the growth on nude mice of solid tumors of human cervical cancer cell line HeLa. Curcumin derivatives had anti-12-O-tetradecanoylphorbol-13-acetate (TPA)-induced inflammatory activity with the same tendency as pol λ inhibitory activity. These compounds might be useful not only as "molecular probes" for pol research, but also as biomedical and chemotherapeutic drugs for anti-cancer or anti-inflammation.